Optimasi Proses Akuntansi di PT Wajah Baru Perkasa: Magang Mandiri - Butar-Butar, Dea Tiara Monalisa; Pangestu, Krisnawati Yeni (Madani: Jurnal Pengabdian Masyarakat dan Kewirausahaan, 2024)
This article discusses the Independent Internship experience at PT Wajah Baru Perkasa, a cement distributor in Batam, with a focus on accounting and finance. The internship activities included recording transactions, preparing financial statements, managing receivables, payroll processing, and optimizing the ERP system. The objective of this internship was to improve the efficiency and accuracy of the company's financial management. The results of this internship showed positive contributions to the company's operations, with several recommendations being implemented. This experience has strengthened the author's skills in facing professional challenges in the field of accounting and finance.